Optimasi Nilai Sun Protection Factor (SPF) Ekstrak Daun Bayam Hijau (Amaranthus hybridus L.) Berdasarkan Variasi Pelarut Etanol 70% dan Aseton dengan Metode Spektrofotometri UV-Vis - Tasya Aurelia; Rahmat Hidayat; Bagas Ardiyantoro (Journal of Innovative and Creativity, 2026)
ABSTRACT Indonesia has high levels of ultraviolet (UV) exposure, which poses a risk of skin health problems. The use of sunscreen is necessary as a protective measure, but synthetic sunscreens can cause side effects, so natural alternatives are needed. Green amaranth leaves (Amaranthus hybridus L.) contain flavonoids that have the potential to absorb UV rays. This study aims to evaluate the sunscreen activity of green amaranth leaf extract using 70% ethanol and acetone solvents, determine the optimum Sun Protection Factor (SPF) value, and identify the most effective and efficient solvent. Extraction was performed using the maceration method, then the sunscreen activity was tested using UV-Vis spectrophotometry at a wavelength of 290–320 nm with concentration variations of 40, 60, 80, 100, and 120 ppm. The results showed that both extracts had sunscreen activity. The optimum SPF value was obtained at a concentration of 120 ppm, namely 70% ethanol extract 11,45 (maximum protection) and acetone extract 19,11 (ultra protection). Acetone was the most effective and efficient solvent in extracting UV-absorbing compounds. Keywords: 70% Ethanol, Acetone, Green Spinach Leaves (Amaranthus hybridus L.), SPF, Sunscreen